Strategy of “Local Centric”: The Impact of Cultural and Brand Identity on Consumer Long-Term Loyalty Baraja Coffee Cirebon - Ririn Ferianti; Rahmadi Rahmadi (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study examines the influence of brand identity and cultural promotion on consumer loyalty. The research uses a quantitative approach with Partial Least Squares Structural Equation Modeling (PLS-SEM) to analyze the relationships between variables. The results show that brand identity has a significant positive effect on consumer loyalty. Cultural promotion also contributes positively to consumer loyalty, although its effect is smaller than brand identity. These findings indicate that strengthening brand identity and integrating cultural promotion strategies can improve consumer loyalty. Therefore, companies should focus on developing strong brand identities while incorporating cultural elements in their promotional activities to enhance customer relationships and loyalty.